The Effect of Self-Construals, Information Exposure, and Consumer Rights Awareness Towards Consumerism and Consumer Independence in Y Generation - Dania Dania; Lilik Noor Yuliati (Journal of Consumer Sciences, 2018)
The raising of competition between business holders causes various cases oflosses that experienced by consumers. Therefore, the consumer independence andconsumerism should be built up to prevent losses due to the crime of businessholders. This study aims to analyze the factors that influence consumerindependence in Generation Y. This research is using an online survey with 291respondents. More than half of the respondents in this research were in themedium category of consumer independence, and were in the low category ofconsumerism. The results of this research showed that independent self-construalshad a significant positive effect toward consumer independence and consumerrights awareness had a significant positive effect toward consumer independenceand consumerism.